Tephrosia Purpurea (Linn.) Pers: A Folk Medicinal Plant Ameliorates Carbon Tetrachloride Induced Hepatic Damage in Rats - B.SANGEETHA; S.KRISHNAKUMARI (International Journal of Pharma and Bio Sciences, 2010)
Herbal drugs are traditionally used in various parts of the world to cure different diseases. The present study has been conducted to evaluate the protective role of the ethanolic extract of the root of Tephrosia purpurea; an important Indian medicinal plant widely used in the preparation of ayurvedic formulations, on CCl4 induced oxidative damage and resultant dysfunction in the liver of rats. The experiments were performed using five groups of animals. The experimental animals were administered with 30% CCl4 in liquid paraffin (1ml/kg bw) for 10 days at 72 hr intervals and the fine crude plant root powder ethanolic extract (EETP) and Silymarin a standard drug, 25 mg/kg bw were fed to the CCl4 treated animals. The effect of EETP and silymarin on Total protein, albumin, bilirubin, cholesterol and glycogen were measured. Further, the effects of the extract on hepatospecific enzymes such as, aspartate transaminase (AST), alanine transaminase (ALT), acid phosphatase (ACP), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and 5’ nucleotidase (5’NT) were estimated. The EETP and Silymarin produced significant effect by decreasing the serum levels of bilirubin and cholesterol whereas Total protein, albumin, glycogen and hepatospecific enzymes were significantly increased. From these results, it was suggested that Tephrosia purpurea protects the liver against CCl4 induced oxidative damage probably by increasing antioxidative defense activities.